Analisis Tahan Luntur dan Ketuaan Warna pada Kain Ecoprint Hasil Teknik Pounding dengan Fiksasi Tawas - Ahmad Satria Budiman; Sri Herlina; Amelia Tri Budi Astuti; Ade Primananda (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Ecoprint is a dyeing technique using natural materials such as leaves, which is increasingly demanded by the textile industry due to its environmental friendliness compared to synthetic dyes. Studies on ecoprinting have mainly focused on leaf patterns and colour directions, with limited research on the colour fastness and strength of leaf parts used on fabrics. The aim of this study is to analyse the colour fastness and strength, specifically on ecoprint fabrics produced by the alum fixation pounding technique, using different types of leaves including teak, lanang, cassava, Japanese papaya and aubergine leaves. The tests include colour fastness to soap wash, ironing heat, sunlight and colour strength value (K/S). The results show that teak leaves have the highest fastness to sunlight with a value of 5 (very good), although they have the lowest resistance to soap washing with a value of 3-4 (fair), while other leaves vary between 3 (fair) and 2 (poor) to sunlight. This reinforces the recommendation to avoid drying ecoprint fabrics in direct sunlight. Fastness to soap wash and ironing heat is considered good. Furthermore, the K/S value analysis shows that the upper side of the leaves generally contributes more to colour absorption than the lower side, depending on the method used, with the exception of manioc leaves.